EVALUASI E-LEARNING MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS (AHP) - Astuti, Cindy Cahyaning; Sari, Herlinda Maya Kumala; Azizah, Nuril Lutvi (PATTIMURA UNIVERSITY, 2020)
E-learning is a learning media that is being used in various universities, although it is not used 100% because some still use face to face. Because it is still new, e-learning needs to be evaluated to make it even better. The purpose of this study is to evaluate e-learning to find out how much the method can be accepted by students. The tool we use to evaluate is the Analytical Hierarchy Process (AHP). The results show that students still prefer face-to-face methods rather than e-learning because face-to-face material is more easily absorbed and interactions with lecturers are more interwoven than using e-learning. But e-learning has the advantage of being more flexible than face-to-face, and gathering tasks are easier with e-learning.